Clothed particle representation in quantum field theory: boost generators of the Poincaré group - Korda, V.Yu.; Frolov, P.A. (Вопросы атомной науки и техники, 2007)
The method of the unitary clothing transformations is used to construct the generators of the Poincaré group in the instant form of relativistic dynamics in the second and third orders in the coupling constant. It is shown that the respective algebra of generators is fulfilled up to the sixth order. The relativistic invariance of the mass and vertex corrections derived is proven. За допомогою методу унітарних одягаючих перетворень побудовані генератори групи Пуанкаре в миттєвій формі релятивістської динаміки в другому і третьому порядках за константою взаємодії. Показано, що алгебра генераторів групи задовольняється до шостого порядку. Обґрунтовано релятивістську інваріантність розрахованих поправок до мас частинок і константі взаємодії. С помощью метода унитарных одевающих преобразований построены генераторы группы Пуанкаре в мгновенной форме релятивистской динамики во втором и третьем порядках по константе взаимодействия. Показано, что алгебра генераторов группы удовлетворяется до шестого порядка. Обоснована релятивистская инвариантность рассчитанных поправок массам частиц и константе взаимодействия.